GLOBAL SURVIVAL BASED ON CLINICAL, HISTOLOGICAL, AND BIOLOGICAL TUMOR CRITERIA IN A SECONDARY PUBLIC BRAZILIAN HOSPITAL - Mosquéra, Júlia Milhomem; Alves, Amanda Ribeiro; Cavalli, Gianna Carolina Pereira; Ramos, Larissa Feitosa de Albuquerque Lima; Vasconcelos, Flávio Lúcio (Mastology, 2021)
Objective: To analyze the overall survival of women with breast cancer based on clinical, histological, and biological tumor data in a secondary hospital in Federal District/Brazil. Method: Retrospective cohort study of women diagnosed with breast cancer from 2012 to 2019, followed up until December 2020, having its data analyzed in 2021. The population studied was from the area covered of the Regional Hospital of Santa Maria (Brasília/Distrito Federal/Brazil), a secondary service, linked to the Brazilian Unified Health System. The information analyzed in this study were state at the last visit (life or dead), the presence of clinically compromised axillary lymph nodes, staging by the TNM system, location of distant metastasis (bone or visceral), histological type and grade, and tumor biological profile. Subsequently, survivals were analyzed in relation to variables previously described. The data were analyzed with the aid of the statistical package SPSS (version 26.0), with p<0.05 is considered significant. Results: This study included a total of 203 patients, of which 158 (77.8%) survived and 45 (22.2%) died. Regarding deaths, 67.5% had a clinically compromised armpit (p<0.001) and 50% were in stage IV (p<0.001). In relation to overall survival, worse survival was observed for patients with clinically suspect lymph nodes (p<0.001), for tumors measuring between 2 and 5 cm and tumors larger than 5 cm in relation to tumors smaller than 2 cm (p<0.001), and for stages III and IV compared to stages I and II (p<0.001). There was no worsening of survival in relation to the histological type (p=0.39), histological grade (p=0.65), location of metastases (bone and visceral) (p=0.76), or biological profile (p=0.40). Conclusion: There were more deaths in relation to the clinically compromised axillary state and in stages III and IV. Larger tumors, more advanced staging, and a clinically compromised armpit worsened overall survival.